MEMAHAMI HADIS MAYIT DI SIKSA SEBAB TANGISAN KELUARGANYA - Isa Ansori (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
Hadith has an important position as the source of the second law after the Qur'an. It is often found that some of the hadith texts appear to conflict with each other either with the text of the hadith itself or the Qur'an. A person especially a hadith and / or legal expert needs to have the ability to complete the texts of the hadith or the Qur'an which sometimes seem to conflict with one another. The hadith about the deceased was tortured because of the crying of his family, is one example of a hadith that is contrary to the word of God that one cannot bear the guilt of others. With the approach of matan criticism (ilmnaqdal-matan), it is obtained that if the text of the hadith contradicts the Qur'anic texts, then the texts because of their qath'i values ​​must be prioritized. Meanwhile, if resolved using the science of mukhtalifal-hadīth, the conflict can be resolved through two ways, namely: First, through al-jam'u which is to compromise these two conflicting traditions, as practiced by Imam Bukhari who explained that the weeping that causes torture is a cry which is traditionalized and done with lamentation; Secondly, through superstitious means, namely maintaining textual understanding of hadith as understood by Umar and Ibn Umar and ignoring the history of Aisha's traditions, is that the deceased was tortured because of the crying of her family, or choosing the hadith as understood by Aisha by ignoring the understanding of Umar and Ibn Umar , as did the critics of Matan Hadith.